PENERAPAN METODE FUZZY C-MEANS DALAM PENENTUAN PENERIMA BEASISWA PROGRAM INDONESIA PINTAR (PIP) - Mardiani Thiaralivta Geraldine Kadja; Nelci Dessy Rumlaklak; Bertha S Djahi (J-ICON : Jurnal Komputer dan Informatika, 2023)
The process of selecting scholarship recipients for Program Indonesia Pintar (PIP) at SMA Negeri 2 Kupang is still done manually by comparing student data. That process can cause the emergence of a reasonably high level of complexity and requires a relatively long time to get the results. Therefore, a Decision Support System (DSS) was built using the Fuzzy C-Means (FCM) method in this study. The FCM method groups data on prospective scholarship recipients with almost the exact resemblance into one cluster. Five (5) criteria are used in selecting PIP scholarships: the number of dependents, parents’ income, water bills, electricity bills and the value of the latest report card. The data is from class XI (eleven) students in 2019 at SMA Negeri 2 Kupang, totaling 422 students. The results of the FCM calculation with a maximum iteration of 100 and an error value of 0.00001 get 240 students entering cluster 1, namely eligible to receive scholarships and as many as 182 students entering cluster 2, namely not eligible to receive scholarships. The testing method used in this study is blackbox testing which is divided into 8 (eight) test scenarios and obtains valid results for all of them. The DSS for determining PIP scholarship recipients using the FCM method is more effective and efficient because it can save time, and scholarships can be awarded to the right students.